The perceptions and experiences of a selected group of classical guitar learners and teachers in the Cape Peninsula - Comninos, Alexander (College of Music, 2023)
Despite the guitar's rich classical tradition, it is primarily viewed as a popular music instrument given its strong associations with popular culture and ubiquitous presence in many popular musics. As a result, classical guitar is often on the fringes of public knowledge and recognition. This study explores how secondary school learners perceive and understand classical guitar. Using a constructivist vision of learning, learners' experiences and perceptions were collected to inform teaching practices. Constructivism is a theory of knowledge that has been used extensively across disciplines to study learning and education. The foundational premise of constructivism is that learners use their prior knowledge and experiences to construct new knowledge. Therefore, collecting and understanding learners' knowledge and experiences is a crucial, preliminary step in facilitating learning and may help teachers better understand their students and help plan teaching strategies that are personal and relevant. Given the constructivist paradigm of this study, the research is primarily qualitative. Questionnaire-based surveys were given to learners and teachers. Learners also participated in a focus-group interview. Using grounded theory, data were analysed, coded, and sorted into emerging themes. The findings showed that most learners were unfamiliar with classical guitar and its repertoire prior to starting lessons. Learners' expectations were primarily based on the guitar's use in popular musics. Learners also reported that the public often equates classical guitar with popular guitar playing styles. In response to peer and/or public perception, learners frequently distinguish classical guitar from popular musics. Using a constructivist lens to analyse the findings, this study has shown that many learners lack the foundational knowledge of classical guitar repertoire. The findings showed that introducing and discussing repertoire with learners may make learning more purposeful. Additionally, this study suggests that learners' musical experiences and preferences should be integrated into the learning process to make learning more relevant. Following the constructivist principles of ‘autonomy' and learner agency, classical guitar learners should also be encouraged to make music-learning part of their everyday lives and not merely classroom activities.